Past, Present, and Future of Anticancer Nanomedicine - Kim K (Dove Medical Press, 2020)
Kyungeun Kim,1 Dongwoo Khang1– 4 1College of Medicine, Gachon University, Incheon 21999, South Korea; 2Lee Gil Ya Cancer and Diabetes Institute, Gachon University, Incheon 21999, South Korea; 3Gachon Advanced Institute for Health Science & Technology (GAIHST), Gachon University, Incheon 21999, South Korea; 4Department of Physiology, School of Medicine, Gachon University, Incheon 21999, South KoreaCorrespondence: Dongwoo KhangDepartment of Physiology, School of Medicine, Lee Gil Ya Cancer and Diabetes Institute, Gachon Advanced Institute for Health Science & Technology (GAIHST), Gachon University, Incheon 21999, South KoreaTel/Fax +82 32 899 1525Email dkhang@gachon.ac.krAbstract: This review aims to summarize the methods that have been used till today, highlight methods that are currently being developed, and predict the future roadmap for anticancer therapy. In the beginning of this review, established approaches for anticancer therapy, such as conventional chemotherapy, hormonal therapy, monoclonal antibodies, and tyrosine kinase inhibitors are summarized. To counteract the side effects of conventional chemotherapy and to increase limited anticancer efficacy, nanodrug- and stem cell-based therapies have been introduced. However, current level of understanding and strategies of nanodrug and stem cell-based therapies have limitations that make them inadequate for clinical application. Subsequently, this manuscript reviews methods with fewer side effects compared to those of the methods mentioned above which are currently being investigated and are already being applied in the clinic. The newer strategies that are already being clinically applied include cancer immunotherapy, especially T cell-mediated therapy and immune checkpoint inhibitors, and strategies that are gaining attention include the manipulation of the tumor microenvironment or the activation of dendritic cells. Tumor-associated macrophage repolarization is another potential strategy for cancer immunotherapy, a method which activates macrophages to immunologically attack malignant cells. At the end of this review, we discuss combination therapies, which are the future of cancer treatment. Nanoparticle-based anticancer immunotherapies seem to be effective, in that they effectively use nanodrugs to elicit a greater immune response. The combination of these therapies with others, such as photothermal or tumor vaccine therapy, can result in a greater anticancer effect. Thus, the future of anticancer therapy aims to increase the effectiveness of therapy using various therapies in a synergistic combination rather than individually.Keywords: stem cell-based therapy, T cell-mediated therapy, macrophage repolarization, nanodrug-based immunotherapy